Missile defense in the United States - Bertil Heurlin (Danish Institute for International Studies (DIIS), 2004)
The basic arguments of this paper are, first, that the current US-missile defense, being operative from fall 2004, is based upon the former experiences with missile defense, second, that missile defense closely associated with weapons of mass destruction has gained the highest priority in American national security policy due to the 9.11 attacks, and third, that the superior argument for establishing an American missile defense is to maintain global, long term political-strategic superiority. The main argument of this brief is that besides the need for meeting current new threats and challenges there are long term agendas behind the US missile defense program: for the United States to ensure a continuing and increasing strategic-political-technological world wide superiority, while at the same time being able to assist allies against WMD-threats from rogue states and rogue actors.
Keywords: 330